Vanilla convolutional neural network is all you need for online and offline signature verification - Yilmaz, Mustafa Berkay; Öztürk, Kagan (Zielona Góra: Uniwersytet Zielonogórski)
Recent advances in deep learning have been utilized successively to improve the performance of signature verification (SV) systems. Deep models proposed in the literature are complicated and need to learn many parameters to give acceptable error rates, requiring a lot of training data. On the other hand, those models are designed and hand-crafted specializing in the problem, online or offline SV.
Keywords: signature verification; representation learning; deep learning; convolutional neural networks